ANALYSIS OF LANDSLIDE HAZARD LEVEL AND DISASTER MITIGATION IN KARANGSAMBUNG DISTRICT OF KEBUMEN REGENCY YEAR 2013 - Rohmah, Rizka Zaenur (Pendidikan Geografi, 2013)
ABSTRACT Purpose of this research was (1) To know the landslide type in Karangsambung District, (2) To know distribution of  landslide hazard level in Karangsambung District, and (3) To know disaster mitigation is that done due landslide in Karangsambung District. This research used spatial description with survey method. The results show that (1) Landslide type in Karangsambung Subdistrict which consist of four types, those are falls, topples, slides, and flows. (2) The level of landslide hazard in Karangsambung subdistrict consist on two class of hazard and distribution as follows: (a) Class II is a high potency of landslide hazard whose large 3.290,92 hectares or 42,14 % and (b) Class III is enough high potency of landslide hazard whose large 4.518,22 hectares or 57,86 %. (3) Disaster mitigation landslide that done techniques and vegetatively by type of landslide include falls, topples, slides, and flows. Keywords: Landslide Hazard Level and Disaster Mitigation